Hubungan Penggunaan Antiretroviral (ARV) dengan Luaran Neonatal pada Ibu Terinfeksi Human Immunodeficiency Virus (HIV) - Ariyani, Noor Aida; Radam, M. Robyanoor Ahyadi; Tobing, Samuel L.; Aditya, Renny; Yunanto, Ari; Andayani, Pudji (Indonesian Journal of Obstetrics & Gynecology Science, 2020)
Tujuan: Mengetahui hubungan penggunaan antiretroviral pada ibu terinfeksi HIV dengan luaran neonatal. Metode: Menggunakan metode analitik dengan pendekatan cross sectional. Pengambilan data dilakukan dari Poli Klinik VCT dan register VK RSUD Ulin Banjarmasin. Jumlah data dibagi berdasarkan penggunaan antiretroviral dan bukan pengguna antiretroviral di hubungkan dengan hasil luaran neonatal berupa berat badan lahir, prematur, IUGR, asfiksia dan kematian neonatal. Analisis menggunakan uji statistik chi square test bermakna bila p < 0.05 ,bila uji chi square tidak memenuhi kriteria maka dilakukan uji fisher.Hasil: Terdapat 73 kasus melahirkan terinfeksi HIV tahun 2015-2018. Ibu terinfeksi HIV yang menggunakan antiretroviral sebanyak 24 (33%) dan bukan menggunakan antiretroviral sebanyak 49 (67%). Dihubungan penggunaan antiretroviral dengan luaran neonatal berat badan lahir bayi, hasil uji square  <0.05 signifikan yaitu  p 0.019,  hasil luaran neonatal prematur (p = 0.022). Hubungan penggunaan antiretroviral terhadap hasil luaran berupa IUGR, asfiksia dan kematian neonatal didapatakan  p 0.166 ; 0.243 ; 0.649.Kesimpulan: Penggunaan antiretroviral pada ibu hamil terinfeksi HIV mengurangi kejadian bayi berat lahir rendah dan prematurRelationship between Antiretroviral Therapy (ARV) with Neonatal Outcome in Woman with HIV InfectionAbstractObjective: Assess the correlation of antiretroviral medication in HIV-infected pregnant women to the outcome of neonates. Method: Analytical method with a cross-sectional approach was used. Data were obtained from the VCT polyclinic and the register of the VK register of Ulin Banjarmasin Regional General Hospital (RSUD). The data are divided into antiretroviral user and non-antiretroviral users linked with the outcome of the neonate in birth weight, prematurity, IUGR, asphyxia, and neonatal death. Statistical analysis using the chi-square test will suggest a significant difference if the p-value is < 0.05. If the chi-square test can not be used, fisher test will be conducted.Result: There are 73 cases of HIV-infected births between 2015 and 2018. There are 24 (33%) of HIV-infected pregnant women on antiretrovirals compared to 49 (67%) non-users. There is a link between antiretroviral usage with the neonatal outcome of birth weight with a chi-square p-value of 0.019 (significant if p-value < 0.05). The outcome of prematurity is also significant, with a p-value of 0.022. The correlation of antiretroviral use to outcome in IUGR, asphyxia, and neonatal mortality are of p-value 0.166; 0.243, and 0.649, respectively.Conclusion: Antiretroviral use in HIV-infected pregnant women reduces the outcome of low birth weight and prematurity incidence in neonates.Key words: HIV, infected woman, outcome, antiretroviral, RSUD Ulin